Development of a high-throughput diagnostic screening tool to monitor the status of pyrethroid resistance in the cattle tick, Rhipicephalus microplus - Maritz-Olivier, Christine (University of Pretoria, 2021)
Dissertation (MSc (Genetics))--University of Pretoria, 2021.